Total synthesis of Met(10)-teixobactin - Gunjal, Vidya B.; Reddy, D. Srinivasa (Tetrahedron Letters, 2019)
The total synthesis of cyclic depsipeptide Met(10)-teixobactin in solution-phase is described. Teixobactin is a structurally and mechanistically novel antimicrobial peptidic natural product with very impressive activities against Gram-positive pathogens. It happens to possess an L-allo-enduracididine (End) residue as part of macrocyclic ring which is not readily accessible. In this report, we have used serine ligation strategy as the key step to prepare an analogue of teixobactin where End being replaced with a readily available amino acid methionine. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: antibiotic; Cyclic tetrapeptides; Serine ligation; Teixobactin